Interval type-2 Fuzzy ARAS method for recycling facility location problems - Karagoz, Selman; Deveci, Muhammet; Simic, Vladimir; Aydin, Nezir (ELSEVIER, 2021)
The management of end-of-life vehicles (ELVs) is currently one of the most important ecological topics. The recycling process has essential importance for the environmental and economic sustainability of the ELV management. Istanbul has the highest rate of car ownership population in Turkey as well as an old vehicle fleet. There is a strong motivation to open an additional ELV recycling facility in this mega-city. Facility location is one of the crucial strategic problems for decision-makers. Addressing multi-criteria and highly uncertain nature of the ELV recycling facility location problem, this paper introduces a novel approach to support the facility location process. For the first time, an extension of the Additive ratio assessment (ARAS) method under the interval type-2 fuzzy environment is presented. The novel method is utilized for solving the ELV recycling facility location problem. The potentials and applicability of the presented interval type-2 fuzzy ARAS method are demonstrated throughout the real-life case study of Istanbul. The comparison with the available state-of-the-art interval type-2 fuzzy set based MCDM methods approves its validity and consistency. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: End-of-life vehicle; Recycling facility location selection; Interval type-2 fuzzy set; ARAS; Multi-criteria decision-making; OF-LIFE VEHICLES; REMANUFACTURING INDUSTRY DEVELOPMENT; MULTIPLE CRITERIA ASSESSMENT; DECISION-MAKING MODEL; REVERSE LOGISTICS; MULTICRITERIA EVALUATION; SUPPLIER EVALUATION; SELECTION; END; ALTERNATIVES; Computer Science